Teaching soft skills in business english class room for tertiary education - Sriranjini, A. (university of Jaffna, 2014)
This research paper deals with the importance of the recent notion of soft skills for work related language coaching, especially its role in Business English. It is argued that soft skills form not only a crucial and increasingly important topic in careers and career negotiations, but are also part and parcel of adult language teaching and learning which tries to take seriously learners' and teacher's personalities. Both a number of general principles and concrete examples of making Soft Skills 'work' in the class-room are discussed. Objective of the Study : To lure the language practitionersto feel the importance of soft skills and make the learners fit for career negotiations. Methodology : Qualitative Results & Conclusion : Notion of soft skills is greatly expected by employers and thus the job seekers should update themselves with this notion to make them fit for the competitive employment opportunities.
Keywords: Business english; Soft skills; Career negotiations; Personality development